2021
DOI: 10.55599/ejssm.v8i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Analyses of the Tri-State Tornado Event of March 1925

Abstract: Severe thunderstorms occurred across portions of the central United States on 18 March 1925. The deadly, long-track Tri-State tornado was the most publicized storm event of 18 March and remains the most significant single tornado in the nation’s history. There has been only one formal paper regarding the Tri-State tornado and its meteorological setting. Results are presented from a recent study of the event that was done drawing upon all relevant Weather Bureau data that could be obtained. The storms of 18 Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Also of interest is the meteorological setting that would have produced such a long-track and violent tornado. That subject is not discussed in this paper, but is described in a companion study by some of the same authors (Maddox et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Also of interest is the meteorological setting that would have produced such a long-track and violent tornado. That subject is not discussed in this paper, but is described in a companion study by some of the same authors (Maddox et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…However, Johns et al (2013) later identified 32 gaps in damage and concluded that there were two separate segments of 280 and 243 km (174 and 151 mi). In addition, an analysis by Maddox et al (2013) showed that the Tri-State Tornado was produced by a supercell with an estimated life-span of 7 h, which moved downstream along a surface warm front at ;26 m s 21 (50 kt). In contrast to that singular long-track storm, the 3-4 April 1974 ''Super Outbreak'' (Corfidi et al 2010) produced 25 F3-F5 tornadoes with pathlengths exceeding 40 km (25 mi) over a geographic area spanning from Michigan south to Mississippi and Alabama.…”
Section: Introductionmentioning
confidence: 99%